Implementasi Pendidikan Agama Islam dalam Membangun Kepekaan Sosial Peserta Didik di SMA Negeri 1 Sangatta Utara - Gilang Tresna Sanubari; Anggra Prima; Satriah (Civiliza Publishing, Indonesia., 2026)
This study aims to describe the condition of students' social sensitivity, analyze the implementation of Islamic Religious Education (PAI), and identify PAI teachers' strategies in building social sensitivity in SMA Negeri 1 Sangatta Utara. The research uses a descriptive qualitative approach with the type of field research. Data were obtained through non-participant observations, structured interviews with two PAI teachers and two students, and school program documentation. Data analysis follows the stages of data condensation, data presentation, and conclusion drawn; The validity of the data is strengthened through triangulation of sources and methods. The results of the study showed that the social sensitivity of students was generally classified as good and reflected in social awareness, empathy, care, social response, and participation in religious and social activities. The implementation of PAI is carried out through Qur'anic tadarus, joint prayer, group learning, discussions, infaq, fundraising, visits to sick school residents, social services, and sharing activities. Teachers' strategies include examples, habituation, advice, strengthening positive behaviors, and involving students in real social experiences. The obstacles found are the use of gadgets and social media which can reduce direct interaction and differences in the level of participation between students. Research confirms that PAI that is integrated with school culture and social practices is able to connect religious knowledge with students' prosocial actions.